Peningkatan Capaian Pembelajaran Siswa Kelas 1 pada Operasi Pengurangan melalui Penerapan Counting Box Media - Nugrahayu, Intan Musyfi'ah (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This research raises a problem, namely whether the use of counting box media can improve student learning outcomes in mathematics learning in class 1 of Sekolah Dasar Negeri Sidorejo 02 Madiun Regency. The aim of this research is to improve the learning outcomes of grade 1 of students at Sekolah dasar Negeri Sidorejo 02 Madiun Regency in mathematics learning through the use of counting box media. This research is a study that uses the classroom action research method. This research design refres to the classroom action research design model of Kemmis dan Mc. Taggart design consists of two cycles and each cycle concists of planning, implementation, observation, and reflection stages. This classroom action research was carried out at SEKOLAH DASAR NEGERI Sidorejo 02, Wunggu District, Madiun Regency. The subjects of classroom action research consistes of all 10 class 1 students. This research was carried out over two cycles. Each cycle action includes planning, implementation, observation, dan reflection. Data collection techniques in this classroom action research use observation methods and written tests. The results of the research show that student learning outcomes have increased. Proven by an increase in student learning outcomes. In cycle I, learning completeness was 70% and increased in cycle II to 90%. Based on the results obtained through classroom action research it can be concluded that the use of counting box media can improve student learning outcomes in mathematics learning in class 1 of SEKOLAH DASAR NEGERI Sidorejo 02 Madiun Regency.